ChemInform Abstract: RhI/RhIII Catalyst‐Controlled Divergent Aryl/Heteroaryl C—H Bond Functionalization of Picolinamides with Alkynes. Issue 6 (21st January 2016) - Martinez, Angel Manu; Echavarren, Javier; Alonso, Ines; Rodriguez, Nuria; Gomez Arrayas, Ramon; Carretero, Juan C.
Abstract: When Rh(I) catalyst is used, the C—H bonds of aryl groups of picolinamides [e.g. (I)] are functionalized to give ortho‐olefinated benzylamines [e.g. (II)] or phenethylamines [e.g. (XIII)].